A Reliable Data Sharing Protocol for Increasing Data Availability in MANET - V. Divya, V. Gokula Krishnan1, Dr. N. Sankar Ram (International Journal of Advanced Science and Technology, 2019)
Mobile Ad hoc Network (MANET) is an indivisible part of wireless network where the nodes are placed randomly. Due to dynamic nature, data availability plays a major role which may degrade the network performance. Data availability defines number of replicated data to be shared between nodes to increase network efficiency. If network partition occurs, the data may not be accessed by the node which leads to network unavailability. In previous work, balancing of data availability and delay was focused. To overcome this issue, a Reliable Data Sharing Protocol (RDSP) is introduced to achieve high data availability and to balance energy efficiency. In first phase of the proposed protocol, neighbor routing is adopted to find reliable node. In second phase, data availability procedure is adopted in the network where the node consumes less energy to replicate the data. In third phase, Cluster is formed to improve data sharing between two nodes and energy model is adopted to improve lifetime of the network. Simulation results are performed on RDSP and existing protocols in terms of throughput, data sharing ratio, packet delivery ratio and computational overhead.Keywords — MANET, Data sharing, Cluster, Reliable node, Scheduling, Packet delivery ration and overhead.